2019
DOI: 10.9734/jemt/2019/v25i230190
|View full text |Cite
|
Sign up to set email alerts
|

Inclination towards Online Shopping - A Changing Trend among the Consumers

Abstract: Shopping was once perceived as an activity of going out, exploring various stores and shops across the town, shifting through a myriad of options and finally settling down to purchase a product with full satisfaction. Now that the technology is skillfully trying to make a person think smartly, without exerting much physical energy, we see that even shopping has been engulfed under grip of changing lifestyle. With online shopping spreading its wings gradually, the experience of ‘touch and feel’ concept is slowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The age category was mentioned as a demographic factor with a strong influence on the dynamics of online commerce, together with a wider group of indicators that contribute, in an aggregated manner, to the explanation and quantification of unobservable variables such as online activity, purchasing behavior in the online environment and the availability/ willingness to spend online (Trocchia & Janda, 2000;Dewalska-Opitek et al, 2022). Devi et al (2019) highlighted the fact that selling in the online environment is the preferred alternative of the young segment who, beyond having the skills to use new information and communication technologies, also show a high willingness to adopt new elements, the risk associated with the use of different platforms for sale being extremely reduced in this segment (Davidavičienė et al, 2020). Other articles that present reasoned results regarding the relationship of the age indicator with the dynamic variable of online commerce were offered by: Sebastianelli et al (2008); Handa and Gupta (2014); Lissitsa and Kol (2016); Herrando et al (2019); Assaker (2020); Liébana-Cabanillas et al (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The age category was mentioned as a demographic factor with a strong influence on the dynamics of online commerce, together with a wider group of indicators that contribute, in an aggregated manner, to the explanation and quantification of unobservable variables such as online activity, purchasing behavior in the online environment and the availability/ willingness to spend online (Trocchia & Janda, 2000;Dewalska-Opitek et al, 2022). Devi et al (2019) highlighted the fact that selling in the online environment is the preferred alternative of the young segment who, beyond having the skills to use new information and communication technologies, also show a high willingness to adopt new elements, the risk associated with the use of different platforms for sale being extremely reduced in this segment (Davidavičienė et al, 2020). Other articles that present reasoned results regarding the relationship of the age indicator with the dynamic variable of online commerce were offered by: Sebastianelli et al (2008); Handa and Gupta (2014); Lissitsa and Kol (2016); Herrando et al (2019); Assaker (2020); Liébana-Cabanillas et al (2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Professional status has also been invoked as a potential discriminator in the manifestation of purchase intention and/or purchase behavior in the online environment (Lissitsa & Kol, 2016;Devi et al, 2019;Ünver & Alkan, 2021). However, there are also studies (Malik & Guptha, 2013;Wu et al, 2016) that invalidated the hypothesis that there is a link between this indicator and the different parameters that define the buying process of individuals in the online environment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that after-sales services played an important role in online shopping. Manorama Devi et al, 3 observed that the young generations were very active in the activities of online shopping and most of them were females. Karthick and Gowtham Aashrivad 4 explored that most of the respondents in the age group of 18 -25 were frequent users of online shopping and most of the females were very much interested in online shopping.…”
Section: Review Of Literaturementioning
confidence: 99%